Evaluating usability of nova Customer Relationship Management (CRM) system in Telekom Malaysia / Muhammad Ashraf Ahmad Fuad - Ahmad Fuad, Muhammad Ashraf (2012)
Customer Relationship Management (CRM) system is becomes a required system in organizations nowadays. This CRM system can help the organization understand about the customer trend and behavior. Hence Telekom Malaysia is applying this system in order to improve the customer experience and gain trust from them. However CRM system has provide the difficulty to the user of the system with several issue such as no status update from system. Users are from customer service field which involve a lot in customer relationship. This issue is related to usability and this study is to provide the evaluation since the system is not yet evaluated. This study also has developed the usability model for evaluation that contains five factors. With the evaluation has been conducted, a recommendation provided after the issues been identify so that developers can make enhancement to the system. This will help to improve the system and enhance the Telekom Malaysia productivity in the customer service area.